Federalism, Veto Power and Coordination of Social Policies in Brazil after 1988 - Machado, José Angelo (Organizações & Sociedade, 2014)
Based on the Brazilian experience post-democratization, the paper reexamines the proposition that federalism obstructs or delays the implementation of social policies, given their dispersive effects and expanded points of veto over national policy. Mobilizes empirical evidence regarding the evolution of intergovernmental transfers for social policies, stressing that the combination of contextual and institutional factors may turn sub-national governments susceptible to the initiatives of the Union. Finally, concludes that federalism is not enough to stop the development of social policies.